The vibrational spectra and the structure of double selenates of sodium - K T Rustembekov (RUDN Journal of Engineering Research, 2009)
For the first time there was synthesized the double selenates of sodium. The composition and the structure of the synthezied compound were determined by methods of X-ray-phase, chemical, atomicemission analysis and IK-spectroscopy.